Antimicrobial stewardship in the emergency department: characteristics and evidence for effectiveness of interventions. (February 2021) - May, Larissa; Martín Quirós, Alejandro; Ten Oever, Jaap; Hoogerwerf, Jacobien; Schoffelen, Teske; Schouten, Jeroen
Abstract: Background: Emergency departments (EDs) are the entrance gates for patients presenting with infectious diseases into the hospital, yet most antimicrobial stewardship programmes are primarily focused on inpatient management. With equally high rates of inappropriate antibiotic use, the ED is a frequently overlooked yet important unit for targeted antimicrobial stewardship (AMS) interventions. Objectives: We aimed to (a) describe the specific aspects of antimicrobial stewardship in the ED and (b) summarize the findings from improvement studies that have investigated the effectiveness of antimicrobial stewardship interventions in the ED setting. Sources: : (a) a PubMed search for 'antimicrobial stewardship' and 'emergency department', and (b) published reviews on effectiveness combined with publications from the first source. Content: : (a) An in depth analysis of selected publications provided four key antimicrobial use processes typically performed by front-line healthcare professionals in the ED: making a (tentative) clinical diagnosis, starting empirical therapy based on that diagnosis, performing microbiological tests before starting that therapy and following up patients who are discharged from the ED. (b) Further, we discuss the literature on improvement strategies in the ED focusing on guidelines and clinical pathways and multifaceted improvement strategies. We also summarize the evidence of microbiologic culture review. Implications: : Based on our review of the literature, we describe four essential elements of antimicrobial use in the ED. Studying the various interventions targeting these care processes, we have found them to be of a variable degree of success. Nonetheless, while there is a paucity of AS studies specifically targeting the ED, there is a growing body of evidence that AS programmes in the ED are effective with modifications to the ED setting. We present key questions for future research.